An Overview of Communication Methods on WiNoC - Smriti Srivastava, Dr. Minal Moharir (International Journal of Advanced Science and Technology, 2020)
Network-on-Chip (NoC) is widely used as a communication infrastructure to obtain an immense parallelism and high degree of integration on a chip. The usage of NoC has been increased due to its faster data processing and increment in the amount of cores present in a single chip. The Wireless Network-on-Chip (WiNoC) is developed as a promising solution to overcome the issues present in the NoC technlogy, such as high delay and power consumption. In this study, the performance and effectiveness of WiNoC architecture is described with its possible communication methods such as unicast, multicast and broadcast routing techniques. This paper analyzes the various communication methods used to route the data packets over the WiNoC. The latency is considered as an important parameter to define the effectiveness of routing over the WiNoC. This comprehensive research helps the researchers to achieve the best solution for the current issues faced in routing techniques over the WiNoC.